Perfil de mutações do vírus da imunodeficiência adquirida tipo 1 associadas à resistência aos antirretrovirais em indivíduos atendidos no município de Catanduva-Noroeste Paulista - Santos, João Ricardo Araujo dos (2012)
The main aim in the use of antiretroviral drugs is delaying the progression of immunodeficiency and restoring, as much as possible, an individual s immunity, increasing the length and quality of life of people living with HIV-1-AIDS. The various polymorphisms presented by HIV-1 may have implications for the pathogenesis, transmission, diagnosis, treatment and development of vaccines which enable an effective prophylaxis. Objective: Describing the resistance profile of HIV-1 to antiretroviral drugs in patients with treatment failure in a reference unit in the treatment of AIDS in the city of Catanduva, Northwestern Region of São Paulo State. Methods: Genotyping tests of 527 patients monitored by the Department of Infectious Diseases belonging to Emilio Carlos School Hospital, located in Catanduva-SP, requested between January 2000 and December 2010 were analyzed. All sequences of the viral genome (TR and PR segment of the pol gene) were analyzed in RENAGENO sites (MS-Brazil) and reanalyzed using Stanford University s algorithm, in order to assess the presence of HIV-1 resistance mutations through updated database. Results: Most analyzed patients were male (58.02%), aged between 40 and 50 years old and had already been subjected to ART. The main therapeutic regimen was 3 ARV, followed by 62.78% of patients. The 184V mutation was the most prevalent (52.7%) among all analyzed ones. There was a high prevalence for TAM: 215Y, 41L, 67N, 210W, 70R, whereas TAM 215F and 219Q were the least frequent ones. Among the multidrug resistance-related mutations, the presence of the 118i mutation may be highlighted in 23.5% of viral genomes. Among the NNRTI mutations, the high prevalence of 103N, found in 28.57% of cases, must be emphasized; 36I mutation was the most frequent among PR leading ones. Conclusion: Analysis of the genomic profile of the virus in the population studied showed that the presence of a specific point mutation does not necessarily increase the resistance of HIV-1 to a certain drug. Interactions among polymorphisms may cause not only resistance but also susceptibility to ART.